The adaptation of plants to resist dry weather - Currie, Jennie Maude (My University, 1900)
Introduction: The two great methods which the plant uses to resist drouth are, 1st, the prevention of over-transpiration and, 2nd, the storing of water. The first head may be divided into the methods used by mature plants, and those used by young plants. These are each sub-divided, and each sub-division will be taken up in its turn. Mature plants resist over-evaporation, first, by surface reduction. This is accomplished in two ways, by fleshy plants and by slender plants. In thick, succulent plants, the cactiform, the stems are fleshy and take the place of leaves. Thus the transpiring surface is reduced in proportion to the volume of the plant. The Euphorbia Cananensis has a very large, long stem and branches, and no leaves, but large prickles. These fleshy plants are found in deserts, and other tracts where the climate is especially arid. Another reduction of surface is accomplished by the asparagus and by switch plants which grow on islands near Australia and in the Mediterranean District. These latter are straight, slender and rigid, and have many long branches which take the place of leaves. They grow close together in large districts. In Australia the chief kind is Papilionaceae; and in the Mediterranean District, the Asparagineae Polygalaceae.
Citation: Currie, Jennie Maude. The adaptation of plants to resist dry weather. Senior thesis, Kansas State Agricultural College, 1900.
Morse Department of Special Collections
Keywords: Climate; Horticulture; Euphorbia Cananensis; Papilioinaceae; Asparagineae; Plygalaceae; Theses; Manuscripts (documents)